(untitled) (Bangladesh Journal of Botany, 2023)
The field experiment was conducted at Tinsukia in Assam of India during kharif seasons of 2016-17 and 2017-18 to investigate the effect of sowing date and nitrogen (N) management practices on the growth and yield of green gram (Vigna radiata L.). Results indicate that the sowing date, S2 (1st September) showed superiority in respect of the growth and yield of the crop, compared to other sowing dates for both years. Amongst the N management treatments, a significantly higher value of the growth parameters, yield attributes, and yields was observed in the treatment receiving 50% N as inorganic fertilizer along with vermi-compost @ 1.0 t/ha. Among the sowing dates, late sown crop (1st October) accumulated the lower heat units (GDD) and higher thermal time (HTU) at 50% flowering and maturity compared to the early sown crop (15th August or 1st September) causing a reduction in seed yield of green gram. The relationship between accumulated growing degree days (AGDD) and yield was positive for all the phenophases with a statistically significant result during PP2 (flowering to maturity). On the contrary, the correlation between AHTU and yield was negative for all the phenophases. The regression models for different phenophases of the crop indicate 86 - 98% of yield variation which can be explained by accumulated agrometeorological variables. Bangladesh J. Bot. 52(2): 323-329, 2023 (June)